Intervention to Reduce Burnout Among Nurses: A Scoping Review - Lestari, Putu Indah Jelita Lestari; Swarjana, I Ketut; Adianta, I Ketut Alit; Sutini, Ni Kadek (Babali Publisher, 2026)
Background: Burnout among operating room nurses negatively affects patient safety and quality of care, highlighting the need for effective and accessible interventions in high-intensity clinical environments. Digital media–based relaxation approaches, particularly smartphone video interventions, offer a low-cost, flexible, and scalable solution. Therefore, this scoping review aims to map and synthesize the existing evidence on interventions to reduce burnout among nurses, with a particular focus on digital relaxation strategies delivered through smartphone videos. Methods: This literature review examined previous research findings in published articles. Article searches were conducted through PubMed and Science Direct using the keywords